MANAJEMEN LABA DAN MOTIF YANG MELANDASINYA - PUTRA ASTIKA, IDA BAGUS (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 1 (2010))
Financial report is a tool of agent’s (management’s) responsibility to principal (owner) in the agency relationship. Recently, more parties need the financial report because the entity has more contract relationships. This contract relationship is called nexus of contracts, which shows how managers and shareholders control costs to maximize the company’s value. In preparing financial report, management uses accrual accounting which is considered able to provide more accurate information than cash accounting due to the possibility of applying matching principle. Earnings management phenomenon exist in financial reporting of an entity because accounting standards still provide opportunities to choose accounting treatment to be used. This would give chance for earnings management to happen. Assumptions laid behind earnings management are opportunistic consideration (personal interest), efficient contract, and decisions made based on accounting income. Earnings management is done through discretionary accruals which is a function of expected income. Various patterns of earnings management include: (1) taking a bath; (2) income minimization; (3) income maximization; and (4) income smoothing.
Keywords: agency relationship, opportunistic behavior and efficient contract, discretionary accrual, and information asymmetry.